Powers of Expression - Clarke David; Holmes Mcdougall (1983)
This book has been designed to prepare students for writing essays and for narrative, descriptive, informative and persuasive writing at first examination level, GCE, SCE and CSE. Introduction, Materials and Methods and Skills, What Being a Writer Means, Three Functions of Language, Planning, Beginnings and Middles and Endings, Structuring, Summary, Structural Patterns, Expressing, Revising, Informative Writing, Imaginative Writing, Narrative, Description, Dialogue, Persuasion and Argument.